Studi Peluang dan Tantangan dalam Pengintegrasian Wellness Tourism dan Budaya Lokal - Raras Wening Pratiti; Monica Adellia Putri; Fidelia Naomi Kartika Aritonang; Wiwik Dwi Pratiwi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Wellness tourism is a significantly growing trend as travelers' interest in holistic health experiences incorporating local culture and traditions increases. The Special Region of Yogyakarta (DIY) is one of the regions that have the potential to develop wellness tourism with a variety of cultural wealth and natural beauty, tourism infrastructure support, commitment to cultural preservation, and the level of demand from tourists. The purpose of this research is to formulate a sustainable and competitive wellness tourism development strategy, both in regional and global markets. This research was conducted using a qualitative approach based on primary and secondary data, mainly through in-depth interviews with relevant parties supported by previous literature studies. The research results are in the form of considerations in developing wellness tourism in Yogyakarta while still integrating local culture and traditional medicine practices as a tourist attraction.